It’s a small world after all: Defining smallholder agriculture in Ghana - Chamberlin, Jordan (International Food Policy Research Institute, 2008)
Strategies for boosting the agricultural economies of developing countries usually focus on small farms, attempting, for example, to link smallholders with markets through production chain development. However, such strategies often fail to differentiate between different types of small farmers or to investigate the distribution of assets within the group—efforts that are important because unequal distributions of assets can restrict pro-poor growth. Further, strategies to develop production chains favor some small farmers over others (i.e., those already participating in targeted chains and those with relatively more productive assets). Using landholding size as an organizational filter, we performed a basic descriptive analysis of smallholder traits in Ghana, using data from the 2005–2006 Ghana Living Standards Survey (GLSS5). We found strong inequalities in landholding distributions within Ghana’s small-farm sector in all regions of the country. Using a classification of smallholders we derived based on landholding size, we examined a variety of small-farm traits and found that many of the broadly perceived defining characteristics of smallholder agriculture—such as low input use and low market engagement—are negatively correlated with landholding size. The crowding of farms at the smaller end of the small-farm spectrum in Ghana suggests that rural development strategies based on expanding existing market chains will face challenges in connecting with the bulk of small producers, who are less well endowed than average statistics indicate.